2012
DOI: 10.1002/jemt.22025
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative process and cell death in salivary glands of Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) semi‐engorged female exposed to the acaricide permethrin

Abstract: Ticks are ectoparasites of great medical and veterinary importance around the world and synthetic chemicals such as permethrin have been used for their control. This study provides a cytochemistry analysis of both degenerative and cell death processes in salivary glands of the brown dog tick Rhipicephalus sanguineus semi-engorged females exposed to 206, 1,031, and 2,062 ppm of permethrin. The results presented herein demonstrate that permethrin is a potent chemical acaricide that would act on the glandular tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
6
12
0
Order By: Relevance
“…The ultrastructural data regarding the salivary glands of the females from the control group corroborate light microscopy analyses by Nodari et al [16][17][18] , who demonstrated that in this group the acini were intact, maintaining original shape; i.e., rounded, and presenting intact cells. The acini I cells presented a well-defined basal membrane labyrinth, as described in literature [22], with randomly distributed mitochondria throughout the cytoplasm and the presence of lipid inclusions (drops).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The ultrastructural data regarding the salivary glands of the females from the control group corroborate light microscopy analyses by Nodari et al [16][17][18] , who demonstrated that in this group the acini were intact, maintaining original shape; i.e., rounded, and presenting intact cells. The acini I cells presented a well-defined basal membrane labyrinth, as described in literature [22], with randomly distributed mitochondria throughout the cytoplasm and the presence of lipid inclusions (drops).…”
Section: Discussionsupporting
confidence: 85%
“…The RNA molecules would also be used in the synthesis of acid phosphatase [29], corroborating Nodari et al [18], who reported intense staining of this enzyme in the acinar cells of female R. sanguineus s. l. salivary glands subjected to these concentrations of permethrin. The presence of this enzyme would be directly associated with the degenerative process of the tissue [18,29], once the increase in the level of activity of the acid hydrolases (acid phosphatase) is a characteristic of autophagic cell death [34,35,[37][38][39][40][41][42].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations